2020
DOI: 10.3389/fimmu.2020.606874
|View full text |Cite
|
Sign up to set email alerts
|

Context Is Key: Delineating the Unique Functions of IFNα and IFNβ in Disease

Abstract: Type I interferons (IFNs) are critical effector cytokines of the immune system and were originally known for their important role in protecting against viral infections; however, they have more recently been shown to play protective or detrimental roles in many disease states. Type I IFNs consist of IFNα, IFNβ, IFNϵ, IFNκ, IFNω, and a few others, and they all signal through a shared receptor to exert a wide range of biological activities, including antiviral, antiproliferative, proapoptotic, and immunomodulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 349 publications
0
17
0
Order By: Relevance
“…IFN-ω shares ∼60% amino acid similarity to IFN-α, the type I IFN more phylogenetically close; in humans only one IFN-ω is produced compared to the 13 IFN-α subtypes ( 30 ). Intriguingly, IFN-ω is still diversifying in many species, including bats and pigs and protect them from excessive tissue damage following infection by several viruses, including Coronaviridae and Orthomixoviridae that can cause severe diseases in humans ( 30 , 31 ). Further data are needed to confirm IFN-ω induction in respiratory mucosal cells and its possible role as an anti-SARS-CoV-2 weapon in our innate responses.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-ω shares ∼60% amino acid similarity to IFN-α, the type I IFN more phylogenetically close; in humans only one IFN-ω is produced compared to the 13 IFN-α subtypes ( 30 ). Intriguingly, IFN-ω is still diversifying in many species, including bats and pigs and protect them from excessive tissue damage following infection by several viruses, including Coronaviridae and Orthomixoviridae that can cause severe diseases in humans ( 30 , 31 ). Further data are needed to confirm IFN-ω induction in respiratory mucosal cells and its possible role as an anti-SARS-CoV-2 weapon in our innate responses.…”
Section: Discussionmentioning
confidence: 99%
“…While all IFN-I share the same components of the canonical signalling pathway, they bind to the receptor with different kinetics and affinities [ 77 , 78 ]. It is conceivable that this could result in differences in downstream kinase activation and IFN-I-subtype specific responses [ 79 ]. Our studies also identified a number of novel phosphosites in the canonical IFN-I signaling molecules STAT1 and IRF9.…”
Section: Discussionmentioning
confidence: 99%
“…In HNSCC, IFNα has the function of immune regulation and inhibition of tumour cell proliferation [ 227 ]. On the one hand, IFNα can resist expansion and induce apoptosis and can also activate autophagy in human nasopharyngeal carcinoma cells.…”
Section: Therapy Options In Hnsccmentioning
confidence: 99%